Micronutrient Status in Patients Following Bariatric Surgery, an Experience From A Developing Country - Shahzeb Khan, Sarzamin Khan, Reema Ghani, Shafqat Ullah, Zia Ullah, Mohammad Zarin, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The scourge of obesity has plagued the developing world, culminating in an exponential rise in related illnesses including diabetes, hypertension, and cardiovascular disease. Bariatric Surgery is the most effective way to achieve substantial weight loss for obese individuals, but its impact on long term micronutrient status needs to be studied in the population of the developing world, as access to a healthy diet remains abysmal. This study aims to assess micronutrient levels in patients who have undergone bariatric surgery and compare the difference in postoperative nutritional complications between Sleeve Gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB). Methodology: This single-center cross-sectional study included 60 patients who underwent bariatric surgery: 30 each for SG and RYGB at Khyber Teaching Hospital, Peshawar. All consenting patients who underwent bariatric surgery and were at a minimum of 6 months post-op were included in this study, whereas patients suffering from malabsorptive disease were excluded. The duration of the study was from January to July, 2023. The data analysis was conducted on SPSS version 25. Results: The mean age of the patients was 40.95 ± 8.34 with a higher proportion of females (68.3%) as compared to males (31.7%). The incidence of total micronutrient deficiencies increased following bariatric surgery (N=62 preoperatively vs N=88 postoperatively). A higher incidence of anemia was reported in RYGB patients as compared to SG (53.33% vs. 16.67%, P=0.003) at 6 months follow up. In addition, both hemoglobin (12.06 ± 0.78 g/dl for RYGB vs. 13.34 ± 1.12 g/dl for SG, P <0.001) and calcium levels (8.3 ± 0.65 for RYGB vs. 8.7 ± 0.53 for SG, P=0.014) were lower in patients who underwent RYGB at 6 months after surgery. Furthermore, in comparison to SG, RYGB patients had lower postoperative levels of Vitamin B12 (451.90 ± 192.87 for RYGB vs. 555.37 ± 188.42 for SG, P=0.040). Conclusion: This study concluded that high risk of micronutrient deficiencies before and after bariatric surgery, necessitating routine screening and supplementation. SG may improve B12 levels and reduce anemia, while RYGB offers better weight loss outcomes. Keywords: Obesity, Bariatric surgery, Roux-en-Y gastric bypass, Sleeve gastrectomy, Nutritional deficiency, Micronutrients.